The Alt Stage and the Po-mo Page: Canadian Spaces for an Anglo-Portuguese Dramaturgy - Jordão, Aida (Theatre Research in Canada / Recherches théâtrales au Canada, 2017)
In this article, Jordão documents the 1991 staging and 2013 publication of her bilingual play Funeral in White . Examining the performance and literary texts, she considers why and how Portuguese and English are used in the play: the conditions that create a space for bilingual theatre and drama in Toronto, the disciplinary requirements of employing two languages on stage and page, and the formal alterations enacted when transitioning from one medium to another. The linguistic dramaturgy of such a project raises several questions. What linguistic conventions will make a Portuguese-English play performable for a cast of English-Canadian actors from a diversity of backgrounds—some who speak Portuguese, others Italian and/or French, and some only English? How will the play be comprehensible to spectators that may be monolingual in English or Portuguese? And, upon publication, will it be accessible to readers who may not master both languages but may have a basic knowledge of Romance languages other than Portugese? Jordão adopts an auto-ethnographic perspective based on her practice to document the playwriting, production, and publication of Funeral in White , and to argue that the sociocultural diversity of theatre makers and spectators is vital to the creation of bilingual theatre.